2023
DOI: 10.2340/actadv.v103.3979
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Spectrum and Clinical Implications of Malignancies in Patients with Bullous Pemphigoid

Abstract: Current research on the malignancy rate and spectrum of malignancies in patients with bullous pemphigoid is contradictory. The aims of this study were to determine the prevalence and spectrum of malignancy in patients with bullous pemphigoid and to compare demographic, clinical, therapeutic and outcome data between bullous pemphigoid patients with and without malignancy. This retrospective cohort study enrolled 335 patients (194 women and 141 men; mean age at diagnosis of bullous pemphigoid 77.5 ± 12 years) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…This conflicts with the conclusions of our study. For example, Baum et al 30 reported a positive correlation between BP and an increased susceptibility to melanoma. Schulze et al 6 noted that patients with BP exhibited an increased risk of hematological malignancies (OR 2.55, 95% CI 2.07-3.13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conflicts with the conclusions of our study. For example, Baum et al 30 reported a positive correlation between BP and an increased susceptibility to melanoma. Schulze et al 6 noted that patients with BP exhibited an increased risk of hematological malignancies (OR 2.55, 95% CI 2.07-3.13).…”
Section: Discussionmentioning
confidence: 99%
“…This conflicts with the conclusions of our study. For example, Baum et al 30 . reported a positive correlation between BP and an increased susceptibility to melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study involving 335 BP patients there was no significant difference in malignancy rates between BP patients and the general population [11]. Consequently, a comprehensive malignancy work-up might not be necessary for BP patients However, the study revealed that BP patients faced a higher risk of melanoma (10.7% vs. 4.3%, p < 0.001), indicating the potential benefit of routine skin screenings [11].…”
Section: Clinical Manifestations and Comorbid Conditionsmentioning
confidence: 97%
“…Among these patients, 127 (87.0%) attained disease control within 4 weeks, defined as the absence of new lesions and itching, as well as the healing of existing lesions [69]. The median (interquartile range [IQR]) time for achieving this control was 14 (7)(8)(9)(10)(11)(12)(13)(14) days [69]. Additionally, 52 (35.6%) patients experienced complete remission, while 13 (8.9%) BP patients relapsed during the observation period [69].…”
Section: Dupilumabmentioning
confidence: 99%